1996
DOI: 10.1128/jb.178.23.6945-6951.1996
|View full text |Cite
|
Sign up to set email alerts
|

Upstream interactions at the lambda pRM promoter are sequence nonspecific and activate the promoter to a lesser extent than an introduced UP element of an rRNA promoter

Abstract: The rightward regulatory region of bacteriophage lambda contains two promoters, p RM and p R , which direct the synthesis of nonoverlapping divergent transcripts from start sites 82 bp apart. Each of the two promoters has an upstream (A؉T)-rich region (ATR) within the sequence from ؊40 to ؊60 where in the rrnB P1 promoter a stretch of 20 (A؉T) bp greatly stimulates promoter function. Here we present an investigation of the possible functional significance of p RM 's ATR. We determined the effects on RNA polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 28 publications
6
39
0
Order By: Relevance
“…In contrast, termination efficiency of T. aquaticus RNAP did not depend on temperature within the range studied ( Fig. 1, lower panel, lanes [1][2][3][4]. The result may indicate that at high temperatures, elongation complexes of T. aquaticus RNAP are more stable than E. coli RNAP complexes.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, termination efficiency of T. aquaticus RNAP did not depend on temperature within the range studied ( Fig. 1, lower panel, lanes [1][2][3][4]. The result may indicate that at high temperatures, elongation complexes of T. aquaticus RNAP are more stable than E. coli RNAP complexes.…”
Section: Resultsmentioning
confidence: 86%
“…Presently, no systematic analysis of upstream promoter sequences of T. aquaticus and related bacteria have been performed, and the specificity of DNA recognition by T. aquaticus ␣CTD remains unknown. Because the deletion of ␣CTDs impaired recognition of T7 A1 and sTap2 promoters, as well as other sTap-based promoters with varying upstream sequences, 4 we propose that at least on these promoters, T. aquaticus ␣CTDs stimulate RNAP binding through favorable but sequence-nonspecific interactions with DNA. Nonspecific contacts of E. coli RNAP ␣CTDs with upstream DNA have been demonstrated to stimulate transcription from promoters that lack the UP element by increasing the rate of RNAP-promoter association (5,6).…”
Section: Roles Of Different Structural Modules Of T Aquaticus Rnap Inmentioning
confidence: 92%
“…(19) showed that the ␣-subunit of RNA polymerase can also interact with an AT-rich sequence (UP element) which is located upstream of the Ϫ35 region of the rrnBp 1 promoter of E. coli and is responsible for enhancement of transcription initiation. Such UP elements appear to be a feature of many promoters (8,19,22).The TyrR protein of E. coli is both a repressor and an activator and controls the expression of a group of eight transcriptional units (TyrR regulon) whose translational products are involved in the biosynthesis or uptake of the three aromatic amino acids (17). The TyrR protein contains three structural domains (5), and genetic analysis has mapped the activation function of TyrR to the N-terminal domain (4,24,25).…”
mentioning
confidence: 99%
“…Work by Ross et al (19) showed that the ␣-subunit of RNA polymerase can also interact with an AT-rich sequence (UP element) which is located upstream of the Ϫ35 region of the rrnBp 1 promoter of E. coli and is responsible for enhancement of transcription initiation. Such UP elements appear to be a feature of many promoters (8,19,22).…”
mentioning
confidence: 99%
“…Therefore, for the wild-type control region, in vitro RNA polymerase (RNAP)-p RM interactions occur almost exclusively in the context of another RNAP already bound to p R . It has been previously shown that this p R -bound RNAP interferes with open complex formation at p RM (16,17,21,34,37). The effect is not exerted at the initial binding of RNAP to the promoter but rather at a subsequent step (16, 34) that is likely a conformational change in the RNAP (9).…”
mentioning
confidence: 97%